Practicing social justice in libraries - Brissett, Alyssa; Moronta, Diana (Routledge guides to practice in libraries, archives and information science, 2022)
Practicing Social Justice in Libraries provides practical strategies, tools, and resources to library and information workers and students who wish to drive change in their classrooms, institutions, and communities, and incorporate social justice into their everyday practice. With contributions from a diverse group of librarians, who have experience working in different types of institutions and roles, the book showcases the actions information professionals, largely from historically marginalized groups, are taking to create a more socially responsible environment for themselves and their communities. The chapters reflect on personal experiences, best practices for programming, professional development, effective collaboration, building inclusive community partnerships, anti-racist practices in the classroom, and organizational culture. Exploring how and why library workers are incorporating anti-racist, and anti-oppressive work within their everyday roles, the book demonstrates that library workers are increasingly sending messages of protest, and advocating for equity, justice, and social change. Highlighting their experiences of marginalization and exclusion, contributors also reflect upon the impact social justice work has on their mental health, careers, and personal lives. Practicing Social Justice in Libraries is essential reading for library and information workers and stude"--